Peningkatan Kemampuan Menulis Puisi dengan Metode Field Trip Siswa Kelas VIII SMPN I Ndona Tahun Ajaran 2023/2024 - Rupa, Josephina Nirma; Ea, Theresia Waso (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
This article aims to provide an overview of the poetry writing abilities of class VIII students at SMPN I Ndona for the 2023/2024 academic year through the use of the field trip method. The problem studied in this research is how to use the field trip method to improve the poetry writing ability of class VIII students at SMPN I Ndona for the 2023/2024 academic year? The approach used in this research is a quantitative approach. Meanwhile, the theories used are writing skills theory, poetry theory, teaching and learning strategy theory, and learning outcomes evaluation theory. The population and sample used in this research were 32 students of SMPN I Ndona for the 2023/2024 academic year.Â  The data collection method is the test method and the data collection technique is the test technique.Â  The data analysis technique in this research uses scoring and statistical techniques. Data presentation techniques use formal and informal techniques. The research results showed that 32 class VIII students at SMPN I for the 2023/2024 academic year were able to write poetry using the field trip method with a percentage of 79.8% in the good category. With details, 20 students got a good assessment and 12 students got a fairly good assessment.